Cardioprotection by systemic dosing of thymosin beta four following ischemic myocardial injury - Pipes, Gordon T. (Frontiers in Pharmacology, 2013)
Thymosin beta 4 (Tβ4) was previously shown to reduce infarct size and improve contractile performance in chronic myocardial ischemic injury via two phases of action: an acute phase, just after injury, when Tβ4 preserves ischemic myocardium via anti-apoptotic or anti-inflammatory mechanisms; and a chronic phase, when Tβ4 activates the growth of vascular or cardiac progenitor cells. In order to differentiate between the effects of Tβ4 during the acute and during the chronic phases, and also in order to obtain detailed hemodynamic and biomarker data on the effects of Tβ4 treatment suitable for use in clinical studies, we tested Tβ4 in a rat model of chronic myocardial ischemia using two dosing regimens: short term dosing (Tβ4 administered only during the first three days following injury), and long term dosing (Tβ4 administered during the first three days following injury and also every third day until the end of the study). Tβ4 administered throughout the study reduced infarct size and resulted in significant improvements in hemodynamic performance; however, chamber volumes and ejection fractions were not significantly improved. Tβ4 administered only during the first three days following injury tended to reduce infarct size, chamber volumes and improve hemodynamic performance. Plasma biomarkers of myocyte injury were significantly reduced by Tβ4 treatment during the acute injury period, and plasma ANP levels were significantly reduced in both dosing groups. Surprisingly, neither acute nor chronic Tβ4 treatment significantly increased blood vessel density in peri-infarct regions. These results suggest the following: repeated dosing may be required to achieve clinically measureable improvements in cardiac function post-myocardial infarction; improvement in cardiac function may be observed in the absence of a high degree of angiogenesis; and that plasma biomarkers of cardiac function and myocardial injury are sensitive pharmacodynamic biomarkers of the effects of Tβ4.